2013
DOI: 10.1089/ten.tec.2013.0011
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation of Functional Epithelial and Epidermal Cells from Human Pluripotent Stem Cells Under Defined Conditions

Abstract: Human pluripotent stem cells (hPSCs) have an unparalleled potential to generate limitless quantities of any somatic cell type. However, current methods for producing populations of various somatic cell types from hPSCs are generally not standardized and typically incorporate undefined cell culture components often resulting in variable differentiation efficiencies and poor reproducibility. To address this, we have developed a defined approach for generating epithelial progenitor and epidermal cells from hPSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The potential of both human ESCs and iPSCs to generate cell lineages from various tissues has fuelled extensive research in the development of methods to differentiate these cells into the specific cell types of interests. To date, differentiation of human ESCs or iPSCs into cardiac 3 , neuronal 4,5 , retinal 6 , hepatic 7 , intestinal 8 , pancreatic 9 and skin 10 have been established with varying efficiencies in the absence of selection or fractionation. With recent advances in differentiation protocols, mature cell phenotypes capable of exhibiting some functional characteristics of adult cells have been established in liver and endothelial and neuronal models 7,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The potential of both human ESCs and iPSCs to generate cell lineages from various tissues has fuelled extensive research in the development of methods to differentiate these cells into the specific cell types of interests. To date, differentiation of human ESCs or iPSCs into cardiac 3 , neuronal 4,5 , retinal 6 , hepatic 7 , intestinal 8 , pancreatic 9 and skin 10 have been established with varying efficiencies in the absence of selection or fractionation. With recent advances in differentiation protocols, mature cell phenotypes capable of exhibiting some functional characteristics of adult cells have been established in liver and endothelial and neuronal models 7,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…These K14+ cells can be terminally-differentiated into epidermal keratinocytes using one of several previously-reported protocols or assays [6,5]. …”
Section: Methodsmentioning
confidence: 99%
“…Consequently, various strategies have been reported utilizing defined culture environments to direct the differentiation of hESCs to epithelial lineage [6,8,12]. Epithelial commitment in feeder-free systems with defined culture milieu is the most promising approach to exclude or minimize the xenogeneic components.…”
Section: Page 7 Of 47mentioning
confidence: 99%
“…They concluded that the cell-ECM interactions are responsible for this discrepancy in proliferation [12]. These differences in growth ability suggest the significant influence of culture microenvironment during differentiation on the subsequent replicative capacity of the keratinocytes.…”
Section: Page 7 Of 47mentioning
confidence: 99%
See 1 more Smart Citation